Alcohol policy compliance among retailers in Bhutan: a multisite community intervention study - Tshewang Gyeltshen; Tshering Penjor; Lham Dorji; Lobzang Tshering; Kinley Dorji; Bhim Nath Subedi; Dorji Tshering; Yvonne Yiru Xu; Gampo Dorji; Ghislain Nono Gueye (BMC, 2021)
Abstract Background Alcohol use is a major public health problem in Bhutan. Compliance with regulations at the point of sale is an important strategy in alcohol control. Retail outlets were briefed on sale regulations and provided notification of rules, which they were directed to display on the premises. The extent to which licensed alcohol outlets responded to possible alcohol purchases was assessed through the use of young proxy-purchasers, adults feigning alcohol intoxication and sober adults. A total of 854 visits (pre versus post visits) were made across four district towns. Two towns (Damphu town in Tsirang district and Pema Gatshel town in Pema Gatshel district) received pre- and post-intervention purchase surveys, while the other two neighbouring towns (Khuruthang town in Punakha and Bajo town in Wangdue) were administered only baseline surveys. Method We used a pre- and post-test community intervention design covering all alcohol retailers both on premise (bar, hotel, restaurant, karaoke bars) and off premise (grocery shops). Compliance with alcohol regulations at the point of sale was assessed through the use of young proxy-purchasers, adults feigning alcohol intoxication and sober adults. Results Retailers rarely checked the age and/or identification (ID) of the proxy-purchasers before the intervention. There was a 22.7% (8.6, 37) percent increase in compliance with laws after the intervention. While some strategies are suggested, the strongest and most effective measure to prevent under-age drinking and service to intoxicated individuals is more rigorous enforcement of existing liquor laws. Conclusion Alcohol control requires ongoing government enforcements, supplemented by public awareness and knowledge.